2013
DOI: 10.3109/13880209.2013.781196
|View full text |Cite
|
Sign up to set email alerts
|

Boehmeria niveaattenuates LPS-induced inflammatory markers by inhibiting p38 and JNK phosphorylations in RAW264.7 macrophages

Abstract: Context: Boehmeria nivea (Linn.) Gaudich (Urticaceae), a natural herb, has a long history of treating several diseases including wound healing. However, the anti-inflammatory effect of B. nivea has not been investigated. Objective: We investigated whether the 70% ethanol extract of B. nivea (Ebn) can exert antiinflammatory activity. Several phenolic compounds of extracts were determined to provide further information on the correlation between anti-inflammatory effects and phenolic compounds. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
(31 reference statements)
3
25
0
1
Order By: Relevance
“…Through cell and animal experiments, we demonstrated the precise antidiabetic efficacy of B. nivea and the mechanisms underlying the effect. The total phenolic content of EBN was 3640 mg/100 g. Several phenolic compounds such as rutin (46.48 mg/100 g), chlorogenic acid (1.96 mg/100 g), luteolin-7-glucoside (11.29 mg/100 g), naringin (1.13 mg/100 g), hesperidin (23.69 mg/100 g), and tangeretin (1.59 mg/100 g) have already been found in EBN [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Through cell and animal experiments, we demonstrated the precise antidiabetic efficacy of B. nivea and the mechanisms underlying the effect. The total phenolic content of EBN was 3640 mg/100 g. Several phenolic compounds such as rutin (46.48 mg/100 g), chlorogenic acid (1.96 mg/100 g), luteolin-7-glucoside (11.29 mg/100 g), naringin (1.13 mg/100 g), hesperidin (23.69 mg/100 g), and tangeretin (1.59 mg/100 g) have already been found in EBN [17]. …”
Section: Discussionmentioning
confidence: 99%
“…While linen and hemp harvesting rely on the microbial retting (degradation) of pectins, ramie is normally extracted by decorticating fresh stems to produce bark ribbons that are subsequently dried, scraped, and de-gummed. Extracts of various parts of the ramie plant have also been reported to have beneficial medicinal properties, including antiviral and anti-inflammatory activities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work suggested that B. nivea has an anti-inflammatory effect on LPS-induced RAW264.7 macrophages by reducing cytokine levels [8]. Thus, we investigated whether B. nivea has an inhibitory effect on an IBD, UC, by using an experimental colitis mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Gaudich (Urticaceae) is a flowering plant that is traditionally used to treat several diseases and heal wounds in Asian countries including China, Korea, the Philippines, and Thailand [7, 8]. Previously, we showed that B. nivea reduces lipopolysaccharide- (LPS-) induced secretion of proinflammatory cytokines such as TNF- α and IL-6 through the inhibition of p38 and c-Jun N-terminal kinase (JNK) [8]; however, the ability of B. nivea to control the effects of DSS-induced colitis has not been investigated. The results of our previous work prompted us to determine whether B. nivea exhibits an anti-inflammatory effect in DSS-induced colitis model mice.…”
Section: Introductionmentioning
confidence: 99%